CORPORATE SOCIAL RESPONSIBILITY DALAM PEMIKIRAN BUDAYA JAWA BERDIMENSI "HAMEMAYU HAYUNING BAWANA” (Pendekatan Studi Hermeneutika) - Pangesti, Resha Dwiayu (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2017)
The purpose of this article is to reveal the meaning that social and environmental accounting can be viewed in the perspective of Hamemayu Hayuning Bawana is oncorporate social responsibility (CSR) program as a form of corporate social responsibility report.The hermeneutical study approach is a method of this researchis used to reveal the meaning of the text of Javanese philosophy Hamemayu Hayuning Bawana by matching the Concept of Cororate Social Responsibility. Theresults of this study explain that thedimension of Hamemayu Hayuning Bawanahas a comprehensive role that every human behavior has relationship with God,human and nature that are synergized so that it can become a guideline in theimplementation of CSR for the sake of business activity. Thecontribution of thisresearch is expected to provide synergy between the value of the philosophy concept of hamemayu hayuning bawana to balance in business activities in order toachieve perfection of life of the company.